2017
DOI: 10.1017/sjp.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

Child Perfectionism and its Relationship with Personality, Excessive Parental Demands, Depressive Symptoms and Experience of Positive Emotions

Abstract: While adaptive perfectionism ensures good overall performance, maladaptive perfectionism is associated with emotional disorders for which psychological treatment is sought. There are many factors that can explain the development of this disorder throughout childhood. The present study analyzed to what extent the child's personality traits and excessive parental demands can predict maladaptive perfectionism, and, in turn, also analyzed how this relates to positive emotions and depressive symptoms in a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
3
9
0
4
Order By: Relevance
“…Despite these potential limitations, this study offers a novel contribution to the scientific community, given that it is the first study to examine the relationship between intrapersonal perfectionism and the components of aggressive behavior (i.e., cognitive, emotional and motor), considering the SOP-C and SOP-S dimensions as separated variables. Moreover, this work also serves to advance the research on childhood perfectionism, a field that has yet to be sufficiently explored (Oros et al, 2017). Instead of the absence of a significant relationship between perfectionist strivings and the dimensions of aggressive behavior, results suggest that children with high levels of self-criticism and a fear of making mistakes tend to be more hostiles, experience more frequent feelings of anger and manifest more aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these potential limitations, this study offers a novel contribution to the scientific community, given that it is the first study to examine the relationship between intrapersonal perfectionism and the components of aggressive behavior (i.e., cognitive, emotional and motor), considering the SOP-C and SOP-S dimensions as separated variables. Moreover, this work also serves to advance the research on childhood perfectionism, a field that has yet to be sufficiently explored (Oros et al, 2017). Instead of the absence of a significant relationship between perfectionist strivings and the dimensions of aggressive behavior, results suggest that children with high levels of self-criticism and a fear of making mistakes tend to be more hostiles, experience more frequent feelings of anger and manifest more aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…So, taking into account this empirical background, it is important to analyze aggressive behavior in children, as well as certain personality traits such as intrapersonal perfectionism, whose manifestations are visible in childhood (Oros, Iuorno, & Serppe, 2017). This goal aims to identify those variables that may act as risk or protective factors of the development of maladaptive patterns of aggressive behavior.…”
mentioning
confidence: 99%
“…People who are high in neuroticism are more probable to respond to emotional stimuli, and they have a low threshold for negative emotions (Minnix and Kline, 2004). Studies have shown a positive relationship between neuroticism and negative affect (Ng, 2009). One of the major emotional stimuli in social interactions is the human face.…”
Section: Introductionmentioning
confidence: 99%
“…Perfectionism has been also associated with a poor therapeutic alliance (van der Kaap-Deeder, Smets, & Boone, 2016) and poor treatment outcomes (for reviews, see Lloyd, Schmidt, Khondoker, & Tchanturia, 2015; Morris & Lomax, 2014). The importance of perfectionism in several psychological disorders has promoted the study of the origin and developmental factors of perfectionism, such as rearing style (Kawamura, Frost, & Harmatz, 2002; Oros, Iuorno, & Serppe, 2017; Soenens, Vansteenkiste, Duriez, & Goosens, 2006).…”
mentioning
confidence: 99%